Armed Criminals in America: A Survey of Incarcerated Felons, 1983 - Wright, James ([Verlag nicht ermittelbar], 1985)
The data for this study were collected using self-administered questionnaires given to a nonprobability sample of incarcerated felons in ten states. Information in the data include socioeconomic status of the inmate, prior criminal record, drug use, weapon usage, family history, and demographic information.